Wanting and willing. (23rd October 2020) - Marcus, Eric
Abstract: How homogenous are the sources of human motivation? Textbook Humeans hold that every human action is motivated by desire, thus any heterogeneity derives from differing objects of desire. Textbook Kantians hold that although some human actions are motivated by desire, others are motivated by reason. One question in this vicinity concerns whether there are states such that to be in one is at once take the world to be a certain way and to be motivated to act: the state question. My question here is different: whether passion and reason constitute distinct sources of human motivation: the source question. In this essay, I defend an affirmative answer to the source question while remaining neutral on the state question. I distinguish between what I call orectic desires, which are associated with the appetites, and anorectic desires, which are associated with judgments of the good. I argue that the two sorts of desires constitute distinct sources of motivation initially on the basis of their differing epistemological profiles. Specifically, self‐attributions of anorectic desires are governed by the transparency condition; self‐attributions of orectic desires are not. It emerges from this discussion that the motivation for performing an action arises in very different ways from each sort of desire.